The effect of primary midwife‐led care on women's experience of childbirth: results from the COSMOS randomised controlled trial. (26th October 2015) - McLachlan, HL; Forster, DA; Davey, M‐A; Farrell, T; Flood, M; Shafiei, T; Waldenström, U
Abstract : Objective: To determine the effect of primary midwife‐led care ('caseload midwifery') on women's experiences of childbirth. Design: Randomised controlled trial. Setting: Tertiary care women's hospital in Melbourne, Australia. Population: A total of 2314 low‐risk pregnant women. Methods: Women randomised to caseload care received antenatal, intrapartum and postpartum care from a primary midwife, with some care provided by a 'back‐up' midwife. Women in standard care received midwifery‐led care with varying levels of continuity, junior obstetric care or community‐based medical care. Main outcome measures: The primary outcome of the study was caesarean section. This paper presents a secondary outcome, women's experience of childbirth. Women's views and experiences were sought using seven‐point rating scales via postal questionnaires 2 months after the birth. Results: A total of 2314 women were randomised between September 2007 and June 2010; 1156 to caseload and 1158 to standard care. Response rates to the follow‐up questionnaire were 88 and 74%, respectively. Women in the caseload group were more positive about their overall birth experience than women in the standard care group (adjusted odds ratio 1.50, 95% CI 1.22–1.84). They also felt more in control during labour, were more proud of themselves, less anxious, and more likely to have a positive experience of pain. Conclusions: Compared with standard maternity care, caseload midwifery may improve women's experiences of childbirth. Tweetable abstract: Primary midwife‐led care ('caseload midwifery') improves women's experiences of childbirth. Tweetable abstract: Primary midwife‐led care ('caseload midwifery') improves women's experiences of childbirth.